2020
DOI: 10.1111/jmwh.13083
|View full text |Cite
|
Sign up to set email alerts
|

Women's Perceptions of Barriers and Facilitators to Vaginal Birth After Cesarean in the United States: An Integrative Review

Abstract: Introduction The purpose of this integrative review was to synthesize the literature on women's perceived barriers and facilitators to achieving a vaginal birth after cesarean. Methods A search of Scopus and PubMed databases and relevant citations from 2000 to 2018 was conducted to identify resources meeting inclusion criteria. Conclusion drawing and verification were completed using data displays, data analysis, and comparison. Results Sixteen resources met inclusion criteria. Factors identified by women with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 53 publications
(242 reference statements)
3
9
0
Order By: Relevance
“…Similar to the findings of our integrative review, 31 researchers in high resource countries have noted that VBAC rates correlate with levels of maternal knowledge about options for birth after cesarean, and access to VBAC supportive providers and birth settings 45‐48 . In this study, as in others, participants viewed their provider as a valuable source of information about pregnancy and birth, 49 and perceived a supportive clinician as a key facilitator for a successful VBAC 31,45,47 . A positive relationship with a provider is of critical importance 50 and provider preference for mode of birth significantly affects a person's choice 51,52 …”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Similar to the findings of our integrative review, 31 researchers in high resource countries have noted that VBAC rates correlate with levels of maternal knowledge about options for birth after cesarean, and access to VBAC supportive providers and birth settings 45‐48 . In this study, as in others, participants viewed their provider as a valuable source of information about pregnancy and birth, 49 and perceived a supportive clinician as a key facilitator for a successful VBAC 31,45,47 . A positive relationship with a provider is of critical importance 50 and provider preference for mode of birth significantly affects a person's choice 51,52 …”
Section: Discussionsupporting
confidence: 89%
“…Their search was complicated by VBAC bans in hospitals, sometimes requiring them to travel more than an hour to obtain a VBAC. Similar to the findings of our integrative review, 31 researchers in high resource countries have noted that VBAC rates correlate with levels of maternal knowledge about options for birth after cesarean, and access to VBAC supportive providers and birth settings 45‐48 . In this study, as in others, participants viewed their provider as a valuable source of information about pregnancy and birth, 49 and perceived a supportive clinician as a key facilitator for a successful VBAC 31,45,47 .…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In a review of women's perceptions of barriers and facilitators to LAC in the United States, Ibrahim et al 16 found lack of practitioner support a significant barrier to women desiring LAC. Bernstein et al 17 prospectively followed LAC candidates through pregnancy and found they were poorly informed about their options and heavily influenced by perceived practitioner preference for mode of birth.…”
Section: Introductionmentioning
confidence: 99%